Oral Health Knowledge, Attitudes, and Practices Among School-Aged Left-Behind Children of the Yao Ethnic Group in Rural Northern Guangxi: A Longitudinal Study - Li, Qiuzhong; Thongmuang, Pimporn; Soontomchai, Sarisak; Qiu, Xiaoqiang (Journal of Roi Kaensarn Academi, 2024)
Background and Objectives: In rural northern Guangxi, the oral health of school-aged left-behind children in Yao ethnic communities has been severely impacted by economic underdevelopment and geographic isolation. This study aims to assess the current status, dynamic changes, and influencing factors of oral health among this population to provide targeted intervention strategies. Methods: A cluster random sampling method was used to select 241 Yao ethnic left-behind children in 2023 and 2024. Oral health examinations and questionnaires were conducted to evaluate dental caries, oral hygiene behaviors, and impacts on quality of life. Data were analyzed using SPSS 26.0 with t-tests, χ² tests, and multivariate logistic regression. Results: The prevalence of dental caries significantly increased to 82.3% in 2024, with a mean DMFT index of 3.67, compared to 54.8% and 2.41 in 2023 (P < 0.05). Fluoride toothpaste use rose by 44.7%, but filling rates remained low at 0.4% and 2%. High-sugar dietary intake increased, and the negative impact of oral health on quality of life was evident. Conclusion: The oral health of Yao left-behind children continues to deteriorate due to poor dietary habits and limited oral health services. Strengthening health education, community support, and preventive treatment is essential to improve their oral health outcomes.